Visualization of the Book: Graphic Metaphors in Art Decoration of Ukrainian Church Editions of the Baroque Epoque - Kurhanova, Olena (Knygotyra, 2023)
The article considers the role of metaphor in the art decoration of 17th–18th centuries Ukrainian editions of church books. It claims that the book art of this period is marked by generous use of symbolic and allegoric visual images which play metaphorical role in general structure of the book. Structural-semiotical exploration of title pages, frontispieces, and illustration cycles in more than one hundred reeditions of Ukrainian church books of 17th–18th centuries enabled us to single out the main types of structure forming visual metaphors. All metaphorical visual images, used in decoration of the church books, transfer the meaning of the book through picturing its author, addressee, or the central theological concept. The image of the author in the tradition of the Ukrainian church book art decoration is inserted in the composition of the title page and frontispiece. It visually presents the church book as a creation of a saint person, inspired by God. The addressee is expressed both by the emblem of a patron, who supported book printing, and by an icon of a divine person to whom the prayer content of the book is addressed. The emblem of a patron is positioned on the title page and/or backside of the title page. It visually generalizes the image of the church book edition, printed due to support of notable person. The icons of a prayer addressee on the backside of the title page, on the frontispieces, or on in-text miniatures, reflect the conceptual idea of a church book as a tool for praying. The main idea of a church book is commonly expressed by symbolic and allegoric compositions. Such compositions, positioned on the title pages and frontispieces, summarize the content of the book by the most unexpected visual images. All the complexity of meanings expressed by images of author, addressee, and theological content, demonstrate the baroque means, which Ukrainian church book editors applied to visualize the church book essence.
Keywords: Ukrainian old-printed books; old-printed church book; book culture; baroque; visual metaphor; book art decoration